2007
DOI: 10.1681/asn.2005121299
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-Brain Natriuretic Peptide

Abstract: This study was performed to determine whether the N-terminal pro-brain natriuretic peptide (NT-pro-BNP) is a useful biomarker in predicting cardiovascular congestion, mortality, and cardiovascular death and event in chronic peritoneal dialysis (PD) patients. A prospective cohort study was conducted in 230 chronic PD patients in a dialysis unit of a university teaching hospital. Serum NT-pro-BNP was measured at baseline together with echocardiography and dialysis indices. Each patient was followed for 3 yr from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
137
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 57 publications
16
137
2
3
Order By: Relevance
“…Wang et al showed that NT-proBNP is an important risk predictor of cardiovascular congestion, mortality, and adverse cardiovascular outcomes in chronic PD patients and adds important prognostic information beyond that contributed by left ventricular hypertrophy, systolic dysfunction, and other conventional risk factors (12). In the study presented here, we found that NT-proBNP was an independent predictor of allcause mortality as well as cardiovascular mortality.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Wang et al showed that NT-proBNP is an important risk predictor of cardiovascular congestion, mortality, and adverse cardiovascular outcomes in chronic PD patients and adds important prognostic information beyond that contributed by left ventricular hypertrophy, systolic dysfunction, and other conventional risk factors (12). In the study presented here, we found that NT-proBNP was an independent predictor of allcause mortality as well as cardiovascular mortality.…”
Section: Discussionsupporting
confidence: 63%
“…ANP and particularly BNP levels are linked independently to left ventricular mass (3-5,8 -16) and function (3,6 -17) and predict total and cardiovascular mortality (1,3,8,10,12,18,40). This The values for peritoneal ultrafiltration represent the lowest quintile of the time-dependent analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations